Analisis Pengaruh Waktu Penangkapan Terhadap Hasil Tangkapan Hand Line Tuna di Laut Maluku - Karyanto, Karyanto; Purwanto, Yuli; Arifin, Muhammad Zainul; Darondo, Franky A.; Katili, Lidya; Fuah, Ricky Winrison (Jurnal Perikanan Unram, 2025)
Girian Bawah Village fishermen use handlines in tuna fishing activities. This study aims to determine the efficiency of fishing time while fishing on the number of tuna handline catches. This study uses catch data with fishing areas in the Maluku Sea during October-November 2022 using the fishing experiment method in a 3-repeat time period, namely morning (05.00 - 09.59), afternoon (10.00 - 14.59) and evening (15.00 - 19.59), then analyzed descriptively quantitatively. Data analysis used statistical tests (Normality Test, Homogeneity Test, ANOVA Test and BNT Test) to see the best time for catching. The results of the normality test obtained normal values, the results of the homogeneity test obtained homogeneous values, the results of the correlation test, have a strong relationship. The results of the ANOVA test show that there is an influence between fishing time and the number and weight of catches. The results of the BNT test, obtained the best time for catching using a tuna handline is the time group 05.00-09.59 WITA or morning time.